A GOVERNMENT FRAMEWORK TO ADDRESS IDENTITY, TRUST AND SECURITY IN EGOVERNMENT: THE CASE OF UAE IDENTITY MANAGEMENT INFRASTRUCTURE - M. Al-Khouri, Ali; Farmer, Muhammad; Qadri, Jameel (European Scientific Journal, ESJ, 2014)
Identity and trust are two important elements that surround anyservice-providing system. They become more critical when such systemsoperate in distributed environments and deal with sensitive details. Thispaper explains how a government-trusted digital infrastructure would addressboth identification and trust requirements and would support thedevelopment of citizen-centric government services. The main contributionof the paper is the presentation of a framework adopted by the government ofthe United Arab Emirates (UAE) that provides a systematic approach tocreating a robust information-sharing system within a secure environment. Amodel is also presented to explain how synergy among institutions is plannedto be achieved and how online users would access web-based governmentservices with a single login using a universal smart identity card.